Bio-green synthesis of calcium acetate from oyster shell waste at low cost and reducing the emission of greenhouse gases - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Nongnuch Laohavisuti; Nattaya Montri; Somphob Thompho; Wimonmat Boonmee; Sorakit Mongkol; Pesak Rungrojchaipon (My University, 2023)
Abstract Bio-green synthesis was designed and employed for calcium acetate monohydrate (Ca(CH 3 COO) 2 ·H 2 O) preparation. Biological wastes obtained from food, oyster shells, were recycled to calcium carbonate and then were used as bio-green raw material to replace limestone/carbonate stone for calcium acetate production. The conditions (ambient temperature occurred in an exothermic reaction, drying time, percentage yield, and percentage solubility) of the reaction between the bio-green CaCO 3 and three different acetic (CH 3 COOH) concentrations (8, 10, and 12 mol·L −1 ) were investigated. The maximum percentage yield (93.42%) with a shorter drying time (18 h) affected the low cost of the product found in the reaction between the bio-green CaCO 3 with 12 mol·L −1 acetic acid. The percentage solubility and chemical compositions without any toxic metal impurity revealed by the XRF technique would be useful to suggest use in the specific application. The XRD, FTIR, and TGA data of Ca(CH 3 COO) 2 ·H 2 O prepared by the bio-green CaCO 3 obtained from oyster shell wastes in this work and those in previous works used other calcium sources were consistent. The morphologies with different sizes of the obtained Ca(CH 3 COO) 2 •H 2 O depend on the CH 3 COOH concentrations reported in this work and were different from those reported in previous works because of different calcium sources. According to the observation, it can be concluded that the low-cost and bio-green technique without the environmental effects was successfully applied to produce cheap Ca(CH 3 COO) 2 •H 2 O and reduce greenhouse gas emissions, which can be used in the specific industry.
Keywords: Calcium Carbonate Crystallization and Inhibition